7c+4b+3b+a+10c-5a=

Simple and best practice solution for 7c+4b+3b+a+10c-5a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7c+4b+3b+a+10c-5a= equation:


Simplifying
7c + 4b + 3b + a + 10c + -5a = 0

Reorder the terms:
a + -5a + 4b + 3b + 7c + 10c = 0

Combine like terms: a + -5a = -4a
-4a + 4b + 3b + 7c + 10c = 0

Combine like terms: 4b + 3b = 7b
-4a + 7b + 7c + 10c = 0

Combine like terms: 7c + 10c = 17c
-4a + 7b + 17c = 0

Solving
-4a + 7b + 17c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7b' to each side of the equation.
-4a + 7b + -7b + 17c = 0 + -7b

Combine like terms: 7b + -7b = 0
-4a + 0 + 17c = 0 + -7b
-4a + 17c = 0 + -7b
Remove the zero:
-4a + 17c = -7b

Add '-17c' to each side of the equation.
-4a + 17c + -17c = -7b + -17c

Combine like terms: 17c + -17c = 0
-4a + 0 = -7b + -17c
-4a = -7b + -17c

Divide each side by '-4'.
a = 1.75b + 4.25c

Simplifying
a = 1.75b + 4.25c

See similar equations:

| 3g+2h-7g+9g= | | 19w=13.5 | | f(x)=x^3-3x^2-8x+30 | | 6(x+5)=3(2x+1)+27 | | 13=-3+4r | | 8d-6e+9e-5d= | | 2x+16=x+21 | | 4x-9=-27 | | 2xy=4+x | | (1-6u+2x)(-8)= | | 11x+10=4x-25 | | 7v+2w-6v-3w= | | 4cosx*4cosx=0 | | 3.68-(6.72+2)= | | 6(4x-4)=3(8x+8) | | -y+5x=13 | | ln(x^3)=9 | | 2a^2+a+1=0 | | 2a=a+12 | | -28x-4(2x-5)= | | 2(2x+3)=2(x+15) | | 6=n^2+3n-12 | | 3(4x+2)=2y-4 | | 8x-4(2x-5)+2= | | -6(-w+3y-2)= | | (3x-2)(5x+1)(4)= | | 6+3q=15 | | 6=10-2w | | 5a-2b-8b+6a= | | 3-2r=2r | | 8x+14+2x=40-(9x+3) | | 2k-4=4 |

Equations solver categories